Development of fermented goat's milk drink (International Seven Journal of Multidisciplinary, 2024)
The goat dairy industry has been growing over the last few decades, with cheese being the product in greatest demand, and as a consequence there is a large generation of whey. This co-product, if disposed of without prior treatment, can cause environmental problems as it has a high biochemical oxygen demand. Making a milk drink is a simple and attractive alternative for using whey. Two formulations of fermented milk drink (40% and 50% whey) were made, with the addition of coffee and amarula flavors, and their physicochemical and sensory quality was evaluated. The pH analysis showed a decrease of 0.3 units for the formulation with 40% whey (FB) over 15 days of storage, corresponding to a 7.5% reduction in pH, which was within the expected value of 3 to 9%. The formulation with 50% whey (FA) had a reduction of 0.4 units. In the evaluation of syneresis, the results showed that after 22 days of storage, the separation of the whey was only 3 cm (16%), remaining stable at this point in both formulations. There was no significant difference between the samples in the sensory analysis for all the attributes evaluated. In addition, there were a variety of perceptions among the tasters, both negative and positive. In this way, the development of a fermented goat's milk drink flavored with coffee and amarula makes it possible to obtain a product with good sensory acceptance, simple to make, high nutritional value and low cost, proving to be a promising alternative for adding greater economic value to goat's whey and milk.